2020
DOI: 10.3389/fpsyt.2020.00422
|View full text |Cite
|
Sign up to set email alerts
|

Altered Temporal Variability of Local and Large-Scale Resting-State Brain Functional Connectivity Patterns in Schizophrenia and Bipolar Disorder

Abstract: Schizophrenia and bipolar disorder share some common clinical features and are both characterized by aberrant resting-state functional connectivity (FC). However, little is known about the common and specific aberrant features of the dynamic FC patterns in these two disorders. In this study, we explored the differences in dynamic FC among schizophrenia patients (n = 66), type I bipolar disorder patients (n = 53), and healthy controls (n = 66), by comparing temporal variabilities of FC patterns involved in spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 68 publications
3
43
0
Order By: Relevance
“…Schizophrenia is a serious mental disorder characterized by a range of symptoms including delusions and hallucinations, 1 and is associated with alterations in brain structure 2 and function. 3,4 Several studies have reported an association between childhood trauma exposure and schizophrenia, in which patients with schizophrenia report higher levels of childhood trauma compared to the general population. 5,6 Moreover, some of the brain alterations observed in schizophrenia have been associated with childhood trauma histories, including altered grey matter volume patterns (eg decreased hippocampus volumes) [7][8][9][10] as well as disrupted brain function (eg decreased connectivity and decreased stability within multiple brain areas) during rest 4,11,12 or specific tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia is a serious mental disorder characterized by a range of symptoms including delusions and hallucinations, 1 and is associated with alterations in brain structure 2 and function. 3,4 Several studies have reported an association between childhood trauma exposure and schizophrenia, in which patients with schizophrenia report higher levels of childhood trauma compared to the general population. 5,6 Moreover, some of the brain alterations observed in schizophrenia have been associated with childhood trauma histories, including altered grey matter volume patterns (eg decreased hippocampus volumes) [7][8][9][10] as well as disrupted brain function (eg decreased connectivity and decreased stability within multiple brain areas) during rest 4,11,12 or specific tasks.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Several studies have reported an association between childhood trauma exposure and schizophrenia, in which patients with schizophrenia report higher levels of childhood trauma compared to the general population. 5,6 Moreover, some of the brain alterations observed in schizophrenia have been associated with childhood trauma histories, including altered grey matter volume patterns (eg decreased hippocampus volumes) [7][8][9][10] as well as disrupted brain function (eg decreased connectivity and decreased stability within multiple brain areas) during rest 4,11,12 or specific tasks. [13][14][15][16] These results highlight the important role of childhood trauma in the development of schizophrenia, as a part of the integrative "bio-psycho-social" model.…”
Section: Introductionmentioning
confidence: 99%
“…Neural variability is altered in mental disorders, including schizophrenia ( Guo et al, 2018 ; Deng et al, 2019 ; Dong et al, 2019 ; Long et al, 2020 ; Zhang et al, 2016 ), major depressive disorder ( Hou et al, 2018 ; Sheng et al, 2018 ; Chen et al, 2019 ), bipolar disorder ( Long et al, 2020 ), attention deficit hyperactivity disorder ( Zhang et al, 2016 ; Zou and Yang, 2019 ) and autism spectrum disorders ( Zhang et al, 2016 ). For instance, in one study, neural variability in the left inferior occipital gyrus was stronger in major depressive disorder patients than in healthy controls ( Hou et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current study was focused on dALFF and dfALFF, which are both voxel-based measures to assess the dynamic fluctuations of local brain activity. Beyond them, there are measures of brain dynamics with a larger scope, such as the temporal variability of functional connectivity (8,9) and stability of modular structures (10) for large-scale brain networks. In my view, future studies are encouraged to investigate the associations between AD and functional brain dynamics by combining both the dALFF/dfALFF and these network-level assessments.…”
mentioning
confidence: 99%
“…In my view, future studies are encouraged to investigate the associations between AD and functional brain dynamics by combining both the dALFF/dfALFF and these network-level assessments. This is important since the aberrant dynamic features of brain function in neuropsychiatric disorders are often observed for the entire brain systems (8,9).…”
mentioning
confidence: 99%